2003
DOI: 10.1021/bi035188o
|View full text |Cite
|
Sign up to set email alerts
|

Probing Ca2+-Induced Conformational Changes in Porcine Calmodulin by H/D Exchange and ESI-MS:  Effect of Cations and Ionic Strength

Abstract: We applied a new method, "protein-ligand interaction using mass spectrometry, titration, and H/D exchange" (PLIMSTEX) [Zhu, M. M. (2003) J. Am. Chem. Soc. 125, 5252-5253], to determine the conformational changes, binding stoichiometry, and binding constants for Ca(2+) interactions with calmodulin (CaM) under varying conditions of electrolyte identity and ionic strength. The outcome shows that CaM becomes less solvent-accessible and more compact upon Ca(2+)-binding, as revealed by the PLIMSTEX curve. The format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
77
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 76 publications
10
77
0
Order By: Relevance
“…Hydrogen-deuterium exchange mass spectrometry (HDX MS) is another approach to examine conformational changes in proteins [39 -42]. For example, Gross et al found that the number of exchangeable hydrogens decreases as the concentration of Ca 2ϩ is increased up to ϳ0.25 mM, which they interpret as a tightening of the Ca 2ϩ binding domains of calmodulin [43,44]. Reactive labeling groups can also be used to monitor protein surface structure [45].…”
mentioning
confidence: 99%
“…Hydrogen-deuterium exchange mass spectrometry (HDX MS) is another approach to examine conformational changes in proteins [39 -42]. For example, Gross et al found that the number of exchangeable hydrogens decreases as the concentration of Ca 2ϩ is increased up to ϳ0.25 mM, which they interpret as a tightening of the Ca 2ϩ binding domains of calmodulin [43,44]. Reactive labeling groups can also be used to monitor protein surface structure [45].…”
mentioning
confidence: 99%
“…We also wish to resolve issues with solubility of insulin in the earlier kinetic results reported in [14], a report in which the kinetics of amide exchange was used without modeling to distinguish various forms of insulin. We now fit the data for r-human, lispro, porcine, and bovine insulins, whose sequences are shown in Table 1, to a kinetic model similar to the one used in [15]. Exchange reactions for proteins and peptides were successfully modeled as pseudo first-order reactions [16], and three exchange rate grouping models were previously applied to the kinetics of exchange of other proteins [15].…”
mentioning
confidence: 99%
“…We now fit the data for r-human, lispro, porcine, and bovine insulins, whose sequences are shown in Table 1, to a kinetic model similar to the one used in [15]. Exchange reactions for proteins and peptides were successfully modeled as pseudo first-order reactions [16], and three exchange rate grouping models were previously applied to the kinetics of exchange of other proteins [15].…”
mentioning
confidence: 99%
“…Thus, an important question is: What is the sensitivity of K 3 and K 4 to the values of the values of K 1 and K 2 that are input into the 4-parameter model? We also posed this question and provided an answer in another article [30]. When the values of K 1 and K 2 were artificially increased or decreased by a factor of 8, both ␤ 3 and ␤ 4 obtained with the 4-parameter fit changed, but K 4 remained nearly constant (within a factor of 1.2), and K 3 only varied within a factor of 2.…”
Section: One To Four Protein-ligand Bindingmentioning
confidence: 98%
“…The percentage of D 2 O was decreased from 99 to 90% in the H/D exchange media to minimize dilution of the protein and to conserve it. The new data were fit by using both the 4-parameter and the 7-parameter models; the results are in Table 3 (the curves were published in our recent article [30]). The relative standard deviation for each binding constant was 40 -70% less than those estimated when using the smaller number of data in the titration.…”
Section: One To Four Protein-ligand Bindingmentioning
confidence: 99%